Prospects of application of modern technologies of remote sensing of the earth in the forest industry - Makunina Yana; Dolmatov Sergey; Orekhovskaya Alexandra; Scherbakov Alexander; Zyryanov Vladimir; Razetdinov Ilgiz (E3S Web of Conferences, 2024)
Currently, forest enterprises are characterized by depletion of forest resources and their significant remoteness. To solve a whole range of tasks related to forest management, monitoring of the environmental situation, control of the forest fire situation, remote sensing systems of the Earth have been developed and, to date, are successfully used. At the moment, such systems are located in almost every region, allowing dispatch centers to quickly perform their work. On the basis of the centers there are several operators who transmit information to the forestry and monitor a lot of video surveillance cameras in real time. Cameras help to detect fires and various smoke points much faster and more efficiently than satellite photography. However, the existing methods for detecting fires in forests have long been outdated and require the introduction of modern auxiliary engineering software solutions in this process. Research and development of systems that allow tracking fires that may be located far from human habitats, and their implementation in the work of forest protection enterprises is a top priority in the Ministries of Forestry.